Penerapan Metode Technique For Order Preference by Similarity To Ideal Solution (TOPSIS) Dalam Pengembangan Desa Terbaik Menggunakan Pembobotan Rank Order Centroid (ROC) - Lakry Maltaf Putra; Warkianto Widjaja (Universitas Budi Darma, 2023)
The best village development is a village development where the village can be used as an example for other villages. However, there are many villages that appear to be the best village developers, but they are not at all. In this day and age there are many people who are reluctant to develop a village, there are also many people who are narrow-minded that there is no need for village development because whether there is or not will definitely remain the same. Therefore the author wants to conduct a study in choosing the best village development by having 5 criteria, namely the number of productive age, the number of umkm, the area of the village, the number of schools, and the number of tourist destinations. So in this research a helper system is really needed to solve the problems that occur in the research. The system referred to as an auxiliary tool in solving problems is (SPK). Based on these problems, a decision support system is needed as a problem solving technique and is assisted by a method that can produce an accurate final value. The method is the TOPSIS method and ROC weighting where the method is very helpful in generating weight values from alternative data and criteria so as to get the final results obtained in Alternative Q6 with a value of 1.00000.